The voice of patients in system redesign: A case study of redesigning a centralized system for intake of referrals from primary care to rheumatologists for patients with suspected rheumatoid arthritis - Elena Lopatina; Jean L. Miller; Sylvia R. Teare; Nancy J. Marlett; Jatin Patel; Claire E. H. Barber; Dianne P. Mosher; Tracy Wasylak; Linda J. Woodhouse; Deborah A. Marshall (Wiley, 2019)
Abstract Background The published literature demands examples of health‐care systems designed with the active engagement of patients to explore the application of this complex phenomenon in practice. Methods This case study explored how the voice of patients was incorporated into the process of redesigning an element of the health‐care system, a centralized system for intake of referrals from primary care to rheumatologists for patients with suspected rheumatoid arthritis (RA)-centralized intake. The phenomenon of patient engagement using "patient and community engagement researchers" (PaCERs) in research and the process of redesigning centralized intake were selected as the case. In‐depth evaluation of the case was undertaken through the triangulation of findings from the document review and participants' reflection on the case. Results In this case, patients and PaCERs participated in multiple activities including an initial meeting of key stakeholders to develop the project vision; a patient‐to‐patient PaCERs study to gather perspectives of patients with RA on the challenges they face in accessing and navigating the health‐care system, and what they see as key elements of an effective system that would be responsive to their needs; the development of an evaluation framework for future centralized intake; and the choice of candidate centralized intake strategies to be evaluated. Conclusions The described feasible multistep approach to active patient engagement in health‐care system redesign contributes to an understanding of the application of this complex phenomenon in practice. Therefore, the manuscript serves as one more step towards a patient‐centred health‐care system that is redesigned with active patient engagement.